FUNCTIONAL NATURE OF CONCEPTUAL OCCURRENCE OF SUBJECT CATEGORY IN ENGLISH - Yuldasheva Dilorom (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2022)
The article illustrates the conceptual occurrence of subject category in the English language. Moreover, it shows its functional nature in the sentences and text.